Pengaruh Laju Irigasi Serta Dosis Bahan Pengkondisi Tanah terhadap Tingkat Penahanan Lengas Tanah dan Produksi Tanaman Pangan dan Hortikultura pada Tanah Pasir - Muhammad Aqil (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
Utilization of coastal plain area for farming are scarce due to the problems faced in the development of those lands such as low fertility, high percolation as well as evaporation rate. Temperature ranges from 40-60°C. In order to increase the utilization of the land, an attempt was done to study the effects of number of manure and irrigation rate on  the yields and soil water extraction of maize, groundnut, tomato and chilly pepper in sandy soil. A series of experiment was conducted from April to December 200I using completely randomized design. The treatments included 4 rates of manure i.e. 10, 15,20 and 25 MT/ha and 4 rates of irrigation I.e. 0.6 I/day, 0.9 I/day, 1.21/day and 1.5 I/day. The result of the experiment showed that the favourable condition to keep moisture content in sandy soil at field capacity and flushing of heat in the soil was achieved at irrigation rate of 1.2 I/day except for tomato which obtained the highest water extraction at irrigation rate of 0.9 I/day. Soil water extraction decreased between 0.15 to 0.55% when irrigation rate were reduced from 1.2 I/day to 0.9 I/day and 0.6 I/day on: maize, groundnut and chilly pepper. The highest yield was obtained at fertilization rate of 20 MT/ha except for maize which obtained the highest yield at fertilization rate of I0  MT/ha. Keywords: Coastal plain, Physical properties, Drip irrigation, Organic fertilizer